The Effect of Local Revenue and Revenue Sharing Funds on Local Expenditures - Azis, Muh. Irfandy; Padliansyah, Roni; Gulabdin, Shaierah Binti; Phin, Ng Yen; Fook, Lim Ming (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2026)
This study aims to analyze the effect of Local Own-Source Revenue and Revenue Sharing Funds on Regional Expenditure in regency/city governments in South Sulawesi Province. This study uses a quantitative approach with secondary data in the form of Local Own-Source Revenue, Revenue Sharing Funds, and Regional Expenditure obtained from the official APBD and TKDD portals. The research sample consisted of 24 regencies/cities in South Sulawesi Province. Data analysis was performed using multiple linear regression with the help of SPSS software to test the proposed hypothesis. The results showed that Local Own-Source Revenue and Revenue Sharing Funds had a positive and significant effect on Regional Expenditure. These findings indicate that the higher the regional fiscal capacity through an increase in PAD and DBH, the greater the ability of local governments to finance public expenditure and development. This study emphasizes the importance of optimizing Local Own-Source Revenue and effective management of Revenue Sharing Funds in order to improve the quality of regional expenditure planning and realization. These findings can also serve as a basis for the government in formulating fiscal policies that are more responsive to regional development needs.